Long-term physical activity: an exogenous risk factor for sporadic amyotrophic lateral sclerosis?. Issue 5 (17th August 2016) - Harwood, Ceryl A.; Westgate, Kate; Gunstone, Sue; Brage, Soren; Wareham, Nicholas J.; McDermott, Christopher J.; Shaw, Pamela J.
Abstract: Objectives : To conduct a geographically defined, UK-based case-control study, to examine any association between physical activity (PA) and amyotrophic lateral sclerosis (ALS). Methods : A novel historical PA questionnaire was designed, validated, and subsequently administered in individual face-to-face interviews of 175 newly diagnosed sporadic ALS cases and 317 age- and sex-matched community controls. Historical PA energy expenditure and time spent in vigorous-intensity PA were derived from questionnaire data and compared between cases and controls. Results : Participation in an extra 10kJ/kg/day of PA (equivalent to approximately 45minutes brisk walking) was consistently associated with an increased risk of ALS, with the strongest association observed for adulthood exercise-related PA (OR 1.47, 95% CI 1.10-1.97). An extra 10mins/day of vigorous PA was also associated with the odds of ALS (OR 1.03, 95% CI 1·01-1·05). Results were slightly attenuated following adjustment for smoking and educational attainment. Conclusions : To our knowledge this is the first study to demonstrate a positive association between ALS and PA participation using a specifically designed and validated historical PA questionnaire. Despite the well-established health benefits of PA, a high activity lifestyle may also be associated with elevated risk of ALS. Large-scale prospective studies in the future may help to confirm this association.